Motives for firms to adopt solid waste management controls the case of food processing sector in Sri Lanka (Journal of Environmental Science and Management, 2014)
This study offers an empirical analysis of the economic incentives available for food processing firms in Sri Lanka to adopt environmental controls for solid waste management. A series of in-depth interviews (n=325) were carried out with managers responsible for environmental quality in five types of food processing firms (coconut-based products, essential oils, non-alcoholic beverages, processed fruits and vegetables, and other processed products). Confirmatory Factor Analysis techniques were applied to the data quantify the effect of six market-based incentives (cost/financial implications, sales, reputation, commercial pressure, human resources and technical efficiency), two regulatory incentives (existing and anticipated government regulations), and the liability incentive on the firm's adoption of solid waste management practices. The level of adoption of environmental practices at the firm level is low - - on average firms adopt only 1.2 compared to the recommended eight different possible practices. Costs of adoption and perceived improvements in technical efficiency are two factors that motivate adoption. Liability laws and anticipated future regulations also matter. The analysis suggests that older and larger firms are more responsive to environmental considerations. Interestingly, export oriented firms do not do better than domestic farms.